Are passive collectors effective samplers of microbes in natural aquatic systems? - Saltonstall, Kristin; Delgado, Jacqueline; Vargas, Marta; Collin, Rachel (Frontiers in Freshwater Science, 2024)
Biodiversity surveys of aquatic systems often include DNA metabarcoding analyses of environmental samples that are collected through filtration of large volumes of water. The standard practice of sterile collection and filtration in or near the field sites is challenging to implement in remote locations, and filtration of large volumes is a limiting step, especially for water from highly productive systems or with high suspended sediment loads. Recent trials have shown that passive samplers can be effective for aquatic metabarcoding to document metazoan diversity, but that this approach needs to be trialed under a wider variety of conditions and across more diverse taxa. Here we assess the utility of passive sampling for documenting the diversity of bacteria in six tropical aquatic environments (1 lake, 1 reservoir, 2 mountain streams and 2 blackwater rivers). We find that passive collectors generally recover significantly higher diversity of Bacteria compared to filtered samples, despite capturing significantly less overall DNA than active water filtering. However, the communities captured by the two methods show significant differences within sites, with only 26% of the Bacteria ASVs recovered by both methods. These differences were largely driven by relative abundances of taxa within Actinobacteriota, Campilobacterota, Desulfobacterota, and Proteobacteria. Our results demonstrate that passive collectors can be a cost-effective solution for monitoring aquatic microbial diversity but that the two methods are not interchangeable. Additional work is necessary to understand the selectivity of both passive collectors and active water filtering for eDNA studies.